Volatilisation and catalytic effects of alkali and alkaline earth metallic species during the pyrolysis and gasification of Victorian brown coal. Part IX. Effects of volatile-char interactions on char–H2O and char–O2 reactivities - Zhang, Shu; Hayashi, J.; Li, Chun-Zhu (Elsevier Science Ltd, 2011)
Volatile-char interactions are an important consideration in the design and operation of a gasifier. This study aims to investigate the effects of volatile-char interactions on the in situ char–steam reactivity at 800 °C and the ex-situ char–O2 reactivity at 400 °C. A Victorian brown coal was gasified in 15% steam at 800 °C in a one-stage novel fluidised-bed/fixed-bed quartz reactor, in which the extent of volatile-char interactions could be controlled. The chars after varying extents of volatile-char interactions and/or varying extents of char conversion in steam were also collected for the measurement of their reactivity with air at 400 °C in a thermogravimetric analyser. Our results show that the char–steam gasification reactions were greatly inhibited by the volatile-char interactions. It is believed that the H radicals generated from the thermal cracking/reforming of volatiles slowed the char gasification in three ways: occupying the char reactive sites, causing the char structure to re-arrange/condense and enhancing the release of catalytic species inherently present in the brown coal. The importance of volatile-char interactions to char–steam reactivity was further confirmed by the char–air reactivity.